4CPS-192 The structures, processes and related outcomes of clinical pharmacy practice as part of the multidisciplinary care of patients with chronic kidney disease: a systematic review. (2nd March 2018) - Raiisi, F Al; Stewart, D; Cunningham, S; Salgado, T; Fernandez-Llimos, F; Fahmy, M
Abstract : Background: Key roles for clinical pharmacists caring for chronic kidney disease (CKD) patients includes: medication management, managing complications, pharmacist-led clinics and independent prescribing. Since the publication of a review by Salgado et al., which reviewed literature to 2010, prescribing practice is continually developing and embedding into clinical pharmacy practice. Moreover, the model of care and advancement in practice is changing and evolving. Hence, there is a need to update the review. Purpose: The main objective of this review is to critically appraise, synthesise and present the available evidence for the structures, processes and related outcomes of clinical pharmacy practice in caring for patients with CKD. Material and methods: The systematic review protocol was developed and published on the PROSPERO database at the Centre for Reviews and Dissemination. Search databases were PUBMED, SCOPUS, CINAHL and IPA. Data assessed and passed for quality were extracted and synthesised. All findings were handled and entered by two independent reviewers to ensure homogeneity and quality. Results: The search identified 37 relevant articles including 10 016 participants. Due to heterogeneity in the data obtained from the included papers, only descriptive synthesis was possible. Eighteen studies (48.6%) reported process indicators and outcome measures, three (8.1%) reported structure, process indicators and outcome measures and one (2.7%) reported structure and process indicators, whereas 16 (43.2%) reported only process indicators. Clinical outcomes were reported in 15 (40.5%) studies, only one (2.7%) study reported humanistic outcomes, clinical and economical outcomes were reported in five (13.5%) studies and three (8.1%) articles reported both clinical and humanistic outcomes. Pharmacists were able to identify 4244 drug therapy-related problems in 2650 patients and made 2537 recommendations to different healthcare professionals with an acceptance rate varying from 33.3% to slightly above 95%. Few studies reported the clinical significance of the recommendations, ranging from moderate to life-saving. Conclusion: There is still a lack of good quality evidence of the role of pharmacists in caring for patients with CKD and the outcomes are diverse. Yet it is apparent, with the best available evidence, that pharmacists caring for patients with CKD may have positive impacts on the outcomes of these patients. Reference and/or Acknowledgements: 1. Salgado T, et al. NDT 2012;27:276–292. No conflict of interest